MENTAL WORKLOAD AND ERGONOMIC ANALYSIS ON PRODUCTION DEPARTEMENT AT PT. XYZ - Pashya Yafi Dhiya; Devi Maulida Rahmah (Universitas Padjadjaran, 2018)
This research aims to identify mental workload on NASA-TLX for mental workload and packaging division and work posture on processing division at PT. XYZ. This research uses RULA and REBA methods for work posture. NASA-TLX (Task Load Index) is used to determine mental work in packaging division. RULA (Rapid Upper Limb Assessment) is used to determine the upper body musculoskeletal disorders (MSDs) injury in the process of production (which consists of weighing and processing station) at PT. XYZ and REBA (Rapid Entire Body Assessment) is used to determine entire body MSDs injury in the production process. Those methods are applied to indicate that the workers are in fact working above the safety limit. Based on NASA-TLX method, it is clear that 21 of 30 workers feel that the work is very heavy. Another case, two unusual postures are found, one is determined by the action level of worker who lifting 20 kgs sack of powder is 10, so the action level of REBA in this case is hardly dangerous. The other one is determined by a worker who entering an ingridient to the machine, weight of the ingridient is 17,05 kgs. It means more than 10 kgs, and thus it can affect body posture. Keywords: Ergonomics, NASA-TLX, REBA, RULA